Practice of correlation analysis for determination of ionospheric influence on GPS measurements - Skeivalas, Jonas (Geodesy and Cartography, 2012)
The variations of ionosphere influence on GPS measurements by correlation analysis of spatial geocentric coordinates are analysed in this paper. The condition of ionosphere is not stable, but it varies with time and space and its influence on GPS measurements relies on geometry of spread GPS satellite signals. There is no stable coordinate’s error of measured point for ionosphere influence. Values of coordinate’s covariations matrix for variation of geocentric rectangular coordinates (X, Y, Z) in single epochs for a definite period. Such values are available for coordinates which are determined by code and carrying phase measurements. The variations of ionosphere electrons content TEC (Total Electronic Content) in the definite period are estimated by values of covariations matrix.Article in Lithuanian.Koreliacinė analizė jonosferos įtakai  GPS matavimams nustatytiSantrauka. Remiantis erdvinių  geocentrinių  koordinačių  koreliacine analize straipsnyje analizuojami jonosferos  įtakos GPS matavimams pokyčiai. Jonosferos būklė  nėra pastovi, ji kinta erdvėje laikui einant, ir jos  įtaka GPS  matavimų  rezultatams priklauso nuo GPS palydovų  signalų  sklidimo geometrijos. Taigi atitinkamai nėra pastovios  matavimo taško koordinačių  klaidos dėl jonosferos  įtakos.  Įvertinti koordinačių  kovariacijų  dėl geocentrinių   stačiakampių  koordinačių  (X, Y, Z) kaitos skirtingose epochose per tam tikrą  laiką  matricų   įverčiai. Tokius  kovariacijų  matricų   įverčius galima skaičiuoti pagal koordinates, nustatytas atliekant kodinius bei nešliofazių  matavimus. Pagal koordinačių kovariacijų įverčių pokyčius įvertinami jonosferos elektronų kiekio TEC (Total  Electronic Content) pokyčiai per tam tikrą laikotarpį.Reikšminiai žodžiai: GPS, jonosfera, kovariacija, TEC.First published online: 03 Aug 2012